ANALISIS YURIDIS RELEVANSI ASAS LEGALITAS DALAM KUHP BARU TERHADAP EVOLUSI KEJAHATAN DIGITAL DI INDONESIA - Padrisan Jamba; Lenny Husna; Diki Zukriadi (Prosiding, 2026)
Rapid technological development in the era of globalization has significantly transformed various aspects of human life, particularly in the digital economy and social interactions within cyberspace. The emergence of Industry 4.0, artificial intelligence, big data, and electronic transaction systems has improved efficiency and accessibility in modern society. However, these advancements are also accompanied by increasing misuse of technology, resulting in various forms of cybercrime such as hacking, online fraud, and other electronic-based criminal activities. This study aims to analyze the relevance of the principle of legality in the new Indonesian Criminal Code (KUHP) in addressing the evolution of digital crime in Indonesia, particularly in response to the rapid development of technology. The research method used is normative legal research with statutory and conceptual approaches, examining the new Criminal Code, the Electronic Information and Transactions Law, and relevant legal literature. The findings indicate that the principle of legality remains a fundamental doctrine in Indonesian criminal law, particularly through the application of lex scripta, lex certa, lex stricta, and lex praevia principles. However, the rapid, cross-border, and technologically complex nature of digital crime creates a regulatory gap, causing law to lag behind social reality. Although the new Criminal Code introduces the concept of living law, it has not fully addressed the complexity of evolving digital crimes. Therefore, harmonization between the Criminal Code, the Electronic Information and Transactions Law, and other sectoral regulations is required, along with adaptive legal reform, to ensure that the principle of legality remains relevant in providing legal certainty, justice, and effective law enforcement in the digital era.